Cyprus : Third Review Under the Extended Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criteria-Staff Report-press Release; and Statement by the Executive Director. (IMF Staff Country Reports; Country Report, 2014)
Cyprus's Third Review Under the Extended Arrangement Under the Extended Fund Facility focuses on strong ownership and implementation of its program. Despite the difficult environment in which the authorities operate, the political commitment remains strong while every effort is being made to maintain strong social cohesion. Steadfast implementation has produced tangible results with indications that the healing process is already under way. Although a difficult adjustment is still ahead, with the guidance of EU and IMF staff, Cyprus has placed itself in a good position to continue along the agreed path.